2019
DOI: 10.1097/inf.0000000000002463
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Antifungal Consumption Is Dominated by Prophylactic Use; Outcomes From The Pediatric Antifungal Stewardship: Optimizing Antifungal Prescription Study

Abstract: AntimicrobiAl reportsBackground: Diagnostic challenges combined with the vulnerability of neonates to develop invasive candidiasis (IC) may lead to antifungal administration in the absence of IC. A modified point-prevalence study was performed to obtain an improved insight and understanding of antifungal prescribing in this specific patient population. Methods: Neonates and infants ≤90 days of age receiving systemic antifungals from 12 centers in England were included. Data were collected prospectively during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 36 publications
1
21
2
Order By: Relevance
“…On the other hand, posaconazole is mainly indicated in the HSCT post-engraftment period and in some primary immunodeficiencies (PID) such as chronic granulomatous disease. These data was quite different from other studies in which fluconazole is the most commonly prescribed agent [7,[11][12][13]. Nonetheless, all these studies include a high proportion, or exclusively include, neonates in whom Candida spp.…”
Section: Clinical Situation Acontrasting
confidence: 58%
See 2 more Smart Citations
“…On the other hand, posaconazole is mainly indicated in the HSCT post-engraftment period and in some primary immunodeficiencies (PID) such as chronic granulomatous disease. These data was quite different from other studies in which fluconazole is the most commonly prescribed agent [7,[11][12][13]. Nonetheless, all these studies include a high proportion, or exclusively include, neonates in whom Candida spp.…”
Section: Clinical Situation Acontrasting
confidence: 58%
“…Nonetheless, all these studies include a high proportion, or exclusively include, neonates in whom Candida spp. is the main and almost only fungal pathogen [7,11,12]. Conversely, for paediatric, particularly children with cancer, PID or HSCT (a majority in our cohort), filamentous fungi should be considered, and other AFs with a broader spectrum play a major role [2,10,18,19].…”
Section: Clinical Situation Amentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies have shown that up to 50% of antifungals are inadequately dosed and that certain antifungals require multiple dose adjustments to achieve therapeutic levels. 5,28,30,31 Our study revealed variability in the target therapeutic levels reported across institutions, which suggests a lack of consensus in current practices and an important opportunity for standardization. Many of the survey respondents reported a lack of confidence in making antifungal recommendations.…”
Section: Discussionmentioning
confidence: 88%
“…26,27 However, fluconazole may represent an important antifungal stewardship target because it accounts for~70% of antifungal prescriptions in children 4 and has been associated with inappropriate prescribing in neonates and children. 1,28 The TDM of azole medications is an important strategy to ensure the appropriate use of antifungals and mitigate adverse events. 29 Most institutions responding to this survey routinely monitor azole levels; however, TDM was the least commonly monitored parameter among ASPs performing PAF of antifungals, and only a few institutions reported having a pharmacokinetics program to assist with antifungal TDM.…”
Section: Discussionmentioning
confidence: 99%